Uji Hedonik dan Mutu Hedonik Susu Nabati sebagai Alternatif Pengganti Susu Sapi - Slamet Hadi Kusumah; Yopi Nugraha; Suci Sopiah (Politeknik Negeri Lhokseumawe, 2026)
The demand for plant-based milk as an alternative to cow's milk continues to rise, yet sensory acceptance remains the main barrier to its adoption. This study aimed to compare the sensory characteristics and panelists' preference for four types of plant-based milk (soy, almond, oat, and mung bean milk) with UHT cow's milk as the control, using hedonic and hedonic quality tests. The evaluation involved 31 untrained panelists assessing commercial samples. The hedonic test measured the liking of five attributes (color, aroma, taste, texture, and overall liking) on a seven-point scale, while the hedonic quality test assessed ten sensory quality attributes on a five-point scale. Data were analyzed using ANOVA followed by Duncan's Multiple Range Test at a 5% significance level. The results showed that UHT cow's milk obtained the highest overall liking (5.65) and the highest overall quality (4.29), differing significantly from all plant-based milks. Among the plant-based milks, overall liking did not differ significantly (4.00–4.55), with mung bean and oat milk numerically highest and soy milk lowest. Almond milk stood out in aroma liking, comparable to cow's milk, whereas the strongest beany aftertaste was found in the legume-based milks (soy and mung bean). Viscosity and sweetness did not differ significantly among samples, while cow's milk excelled in color, homogeneity, mouthfeel, and creaminess. Sensorially, plant-based milks have not yet matched cow's milk, but mung bean and oat milk are the most promising for development through improvements in taste, aroma, beany aftertaste, and creaminess.